Whole-Body Cryotherapy: Potential to Enhance Athlete Preparation for Competition? - Partridge, Emily M.; Cooke, Julie; McKune, Andrew; Pyne, David B. (Frontiers in Physiology, 2019)
The final hours of preparation before competition are important for performance. Recovery, preparation and warm up protocols are evolving continuously and include passive and active modalities often developed by “trial and error” approaches. Passive modalities, such as whole-body cryotherapy (WBC), have the potential to enhance both recovery and preparation. Whole-body cryotherapy has generally been used within a recovery setting after competition or strenuous training for athletes, and in clinical settings for the general population. However, the acute hormonal, anti-inflammatory, perceptual and psychological responses yielded by a single, or repeated, bouts of WBC indicate that this practice could enhance an athlete’s competition readiness when used alongside traditional elements of active warm-ups in the hours before competition in addition to aiding recovery in the hours after. Here we summarize and evaluate the acute effects of WBC exposures on physiological, performance and perceptual responses, and examine the likelihood these responses could theoretically translate into enhanced athletic performance. The potential to enhance an athlete’s performance using acute passive WBC exposure is a novel intervention that requires further investigation.